Chemotherapy for Metastatic Breast Cancer – An Anachronism in the Era of Personalised and Targeted Oncological Therapy? - Schneeweiss, A.; Ruckhäberle, E.; Huober, J. (Geburtshilfe und Frauenheilkunde, 2015)
Based on the findings of modern molecular biology, breast cancer is nowadays considered to be a heterogeneous disease. This leads to the objective of an individualised, more patient-oriented therapy. A series of target molecules for this purpose has already been identified. The principle of targeted oncological therapy was realised decades ago with the introduction of endocrine therapy for patients with hormone receptor-positive tumours. The modern therapy for HER2-positive tumours is a further example for the translation of targeted therapy into clinical routine. For patients with HER2-negative metastatic breast cancer, to date two targeted drugs, bevacizumab and everolimus, are available for routine clinical use. Many other substances are still undergoing clinical development. However, validated predictive markers to aid in therapeutic decision-making and therapy control are still lacking. Chemotherapy constitutes an effective palliative therapy with proven efficacy for the patients. In this process strategies have also been realised for a targeted therapy against tumour cells with the help of chemotherapeutic agents such as, for example, the intracellular activation of the prodrug capecitabine or the active albumin-mediated transport of nab-paclitaxel which leads to higher peri- and intratumoural enrichments. The continuing unchanged relevance of chemotherapy is often underestimated in the current discussions and will be comprehensively evaluated in this review.
Keywords: metastatic breast cancer; HER2-positive; HER2-negative; targeted therapy; chemotherapy